The Sentimental Community: A Site of Belonging. A Case Study from Central Australia - Holcombe, Sarah (The Australian journal of anthropology, 2004)
The concept of ‘community’ has a deep genealogy, extending from the classical social science literature of the nineteenth century to its wide and confused employment in policy contexts and textual analyses discourses. This paper will focus on one aspect of a community whose lineage extends theoretically from the communal concept of a ‘consciousness of kind’. In the desert community of Mount Liebig, known locally as Amunturrngu, the sentimentalised elements of this shared consciousness have evolved from principles of land tenure that have adapted to the newly settled environment. These sentimental signifiers are drawn from the country on which this community developed and the constructions of place that settlement has actively encouraged. To this end the concepts of reterritorialisation and religious egalitarianism will be explored, principally through the medium of inma kuwarritja (new ritual) in order to analyse how people affiliate with and embody a reterritorialised identity through the traditional imagination. How does this embodiment of country affect the settlement process, whereby a community is constructed?